Georgia Architectural and Historic Properties Survey of Cherry St., Rebecca, Turner County, Ga., March 1981 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Cherry St., Rebecca, Turner County, Ga., March 1981. 1 story rectangular clapboard under asbestos shingles. No porch. Double hung sash windows with 2/2 lights. Poor condition. Date of Construction: c. 1890. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Cherry St., Rebecca, Turner County, Ga., March 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 83.7 MB (87,854,812 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Rebecca (Ga.); Turner County (Ga.)